Thyroid Metastasis from Nonsmall Cell Lung Cancer - Tariq Namad; Jiang Wang; Ralph Shipley; Nagla Abdel Karim (Case Reports in Oncological Medicine)
Background. Thyroid metastases are rare. Clinically, they represent less than 4% of thyroid malignancy in clinical studies. Aim. To assess various presentations and therapy for patients with lung cancer metastatic in the thyroid. Materials and Methods. We report a case of metastatic adenocarcinoma of the lung to the thyroid. We reviewed similar reports through PubmMed search from 1997 until 2013. Case Presentation. A 48-year-old lady was seen in the clinic for an adenocarcinoma of left upper lobe (LUL) of the lung; she received neoadjuvant chemotherapy then LUL lobectomy. After 9 months she presented with diffuse goiter initially believed to be a solitary metastatic lesion as it was positive for adenocarcinoma of lung origin on histopathological exam with TTF-1 positivity. Unfortunately, PET scan showed additional mediastinal lymphadenopathy. Conclusion. The treatment strategy for metastatic thyroid disease is based on a multidisciplinary approach, where thyroidectomy would have been considered in case of a solitary metastatic involvement, but further metastatic workup is mandated to direct further systemic therapy versus palliative radiation therapy.